A Novel Model-Free Intelligent Proportional-Integral Supertwisting Nonlinear Fractional-Order Sliding Mode Control of PMSM Speed Regulation System. (28th September 2020) - Gao, Peng; Lv, Xiaodong; Ouyang, Huimin; Mei, Lei; Zhang, Guangming
Abstract : This study proposes a novel model-free intelligent proportional-integral supertwisting nonlinear fractional-order sliding mode control (MF-iPI-ST-NLFOSMC) strategy for permanent magnet synchronous motor (PMSM) speed regulation system. First of all, a model independent intelligent proportional-integral (iPI) control strategy is adopted for the motor speed regulation system. Next, a novel model-free supertwisting nonlinear fractional-order sliding mode control (ST-NLFOSMC) strategy is constructed based on the ultralocal model of PMSM. Meanwhile, a linear extended state observer (LESO) is used to estimate the unknown terms of the ultralocal model. Then, this study presents the novel hybrid MF-iPI-ST-NLFOSMC strategy which integrates the model-free ST-NLFOSMC strategy, the model-free iPI control strategy, and the LESO. Moreover, the stability of the proposed hybrid MF-iPI-ST-NLFOSMC strategy is proved by the Lyapunov stability theorem and fractional-order theory. Finally, the simulations and comparison results verify that the hybrid MF-iPI-ST-NLFOSMC strategy proposed in this paper has better performance than the other model-free controllers in terms of the static characteristic, dynamic characteristic, and robustness.